Opportunity to learn the content of mathematics in Pisa 2012 - Bacchetto, João Galvão (2021)
The Programme for International Student Assessment] (Pisa) 2012 used student-level questionnaires to evaluate the Opportunity to Learn Content defined as students’ exposure to subject content in school – in this case, specifically in the area of Mathematics. Based on the results of the questionnaires, three indexes related to students’ performance in a group of countries were generated. The study suggests that there is a relationship between two of the indexes and the mean scores in the Mathematics test, but this relationship is weak for the third index. These results can elucidate aspects about exposure to mathematical tasks and concepts in the classroom which are not always well known.